Investigating the Intrinsic Factors Affecting Students’ Motivation to Complete Their Doctoral Degree in Southern Punjab - Imtiaz, Mehwish; Haider, Syed Zubair; Munawar, Uzma (Pakistan Journal of Humanities and Social Sciences, 2023)
Motivation describes the process of encouraging and influencing someone to perform in a particular way. The process that starts, directs, and sustains goal-oriented behaviors is known as motivation. There are two types of motivation the first one is intrinsic motivation and the second is extrinsic motivation. The main focus of the current study was intrinsic motivation. The purpose of the study was to find out the intrinsic motivational factors’s affect doctoral students’ performance and to identify how these intrinsic motivational factors have an impact on doctoral degree completion. In the current study, a descriptive method of research was used. So for data collection, a questionnaire was used to take the required information from PhD research scholars. The sample of the study was 100 PhD research scholars from the universities of Southern Punjab such as The Islamia University of Bahawalpur, Bahudin Zikriya University Multan, Government Sadiq College Women University Bahawalpur, and Women University Multan. Based on the analysis of the study majority of students agree that the thesis writing process is interesting. Students, on average, express a high level of interest in learning new things about research. The study further explains that students agreed to some extent that they face problematic situations in conducting research. Moreover, students somewhat agree that the literature in doctoral studies is demanding and extensive.